Evaluating Oregon’s Justice Reinvestment Act: An Interrupted Time-Series Regression of State-Level Outcomes - Dollar, Christopher W. (Crime & delinquency, 2024)
Many jurisdictions across the U.S. have adopted justice reinvestment initiatives (JRIs) as a strategy for reducing the use of incarceration and mitigating large correctional budgets. In spite of this widespread adoption, little empirical research has explored the impacts of justice reinvestment policies. In response, this study employed quasiexperimental, interrupted time-series regression analyses using a decade of monthly court and corrections data to assess if JRI legislation in Oregon was effective. Results show decreased prison usage and recidivism, as well as reveal delayed and significant trend changes for felony jail admissions and community corrections populations as a result of the JRI legislations. A course for future research to further advance understanding of reinvestment and resource reallocation is outlined.